2022
DOI: 10.1002/eap.2508
|View full text |Cite|
|
Sign up to set email alerts
|

Emerald ash borer intensifies harvest regimes on private land

Abstract: Invasive forest insects have significant direct impacts on forest ecosystems and they are also generating new risks, uncertainties, and opportunities for forest landowners. The growing prevalence and inexorable spread of invasive insects across the United States, combined with the fact that the majority of the nation's forests are controlled by thousands of autonomous private landowners, raises an important question: To what extent will private landowners alter their harvest practices in response to insect inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Salvage logging is also more likely to amplify disturbance in systems in which the host tree species is less abundant. For example, Holt et al (2022) found that timber harvest intensity was greater in forests infested with the rapidly expanding borer insect Agrilus planipennis Fairmaire (emerald ash borer, EAB). Further, about half of the total harvest, on average, was from species other than Fraxinu s, which is EAB's host.…”
Section: Discussionmentioning
confidence: 99%
“…Salvage logging is also more likely to amplify disturbance in systems in which the host tree species is less abundant. For example, Holt et al (2022) found that timber harvest intensity was greater in forests infested with the rapidly expanding borer insect Agrilus planipennis Fairmaire (emerald ash borer, EAB). Further, about half of the total harvest, on average, was from species other than Fraxinu s, which is EAB's host.…”
Section: Discussionmentioning
confidence: 99%